Opinión pública y represión en Yucatán: 1808-1816 - Machuca Gallegos, Laura (El Colegio de México, A.C., 2017)
Across the Hispanic world, the first two decades of the 19th Century were characterized by the development of a new political force called public opinion. The objective of this article is to analyze its appearance in Merida, Yucatan: though far from the great centers of power, this city actively participated in the same political, social and cultural processes as the rest of ibero-America in the period starting in 1808. The author centers their attention on the Sanjuanistas, a group active during this time whose goal was to defend the Constitution of Cadiz. Yucatan, far from representing  a local case, instead reveals the ins and outs of new forms of sociability, above all in the field of political practices, and their embrace by society.